2007
DOI: 10.1177/1046878107308059
|View full text |Cite
|
Sign up to set email alerts
|

The life of a simulation: Programmatic promises and pitfalls

Abstract: This article is a reflection on the promises and pitfalls of using a simulation-centered curriculum for English as a Second Language (ESL) writing over time. A one-time graduate student and instructor of the program, the author returned after 10 years to the program as the director to discover that as with any curriculum, changes had occurred-changes in leadership, teaching staff, and course objectives-which had consequences for simulation use in the classroom. In an effort to determine the current state of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Pedagogical games, also known as serious games, are regarded as tools to provide an enhanced learning experience (Pasin & Giroux, ). Such games, however, may be costly to develop or adopt for teaching (Damron, ). The literature shows examples of free and easy to adopt games used to enhance learning in operations and supply‐chain management classes.…”
Section: Introductionmentioning
confidence: 99%
“…Pedagogical games, also known as serious games, are regarded as tools to provide an enhanced learning experience (Pasin & Giroux, ). Such games, however, may be costly to develop or adopt for teaching (Damron, ). The literature shows examples of free and easy to adopt games used to enhance learning in operations and supply‐chain management classes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers and educators alike have recognized the usefulness of a simulation-centered curriculum in the language classroom (e.g. Damron, 2008; Halleck, 1990; Ruben, 1999; Salies, 2002a, 2002b).…”
mentioning
confidence: 99%
“…The faculty members pointed out an improvement in student engagement and class participation as important outcomes of using games in the classroom. Furthermore, Damron (2008) analyzed the perceptions of 12 former and current instructors regarding the use of simulations in the International Composition Program at Oklahoma State University in order to generate some future directions of the program. One the one hand, the instructors indicated that simulations assist students with building schema and developing collaboration, argumentation, and critical thinking skills as well provide a venue to practice all the four skills and express personal views.…”
mentioning
confidence: 99%